The Counter-Cultural Church: An Analysis of the Neo-Anabaptist Contribution to Missional Ecclesiology in the Post-Christendom West - Paas, Stefan (Ecclesiology, 2019)
In response to the ongoing secularization of the West, much missiological reflection on the church has turned to post-foundationalist, pragmatic and traditioned approaches culminating in a counter-cultural' model of the church. This model, developed most extensively in neo-Anabaptist contributions, is believed to contain rich promises for missionary ecclesiology in a post-Christendom age. In this article several traditions that have contributed to this approach are examined, with an emphasis on neo-Anabaptism - especially the works of Yoder and Hauerwas. A critical discussion of the model's idealism and view of culture follows. Based on this analysis, the article discusses how the model of the counter-cultural church can contribute to Christian mission in the secularized societies of the West.